LABOR AND PAYMENT ACCOUNT - Mirzayev Ravshanjon Burkhanovich; Baltabayeva Malokhat Ortiqaliyevna; Rakhimova Mashrabkhan (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
the article provides a comprehensive description of the payment of wages and the procedure for the payment of wages commensurate with labor. It also reflects the changed statistical conditions of the minimum wage of the Republic of Uzbekistan over the years.